Study, Design, Modeling, Simulation, and Control Analysis of DC-DC Power Converters - Salam Waley Shneen (Journal of Fuzzy Systems and Control, 2025)
Researchers are interested in studying power electronics converters because of their importance in many fields and applications, including industrial, agricultural, and domestic applications. Power electronics converters are relatively economical compared to conventional converters. In this work, the researchers present research contributions, including a study on how to design a DC-DC converter from a constant electrical quantity at the converter's input to a variable quantity depending on the load requirements associated with the converter's output. As another research contribution, the researchers are working on building a model of a DC-DC converter. The third contribution is conducting tests using the model and simulating the converter using the engineering computer program MATLAB. Performance is evaluated, ways to improve the converter's operation are identified, and its behavior is analyzed during the transient and steady-state operation periods. Power electronics converters are used to increase the voltage, called a boost converter. There is a type used to decrease the voltage, called a buck converter. Another type combines both states, depending on the system requirements, called a buck-boost converter. Tests are conducted to identify how the converter can be used to meet the load requirements associated with the converter output. They also identify how to control system state changes during operation and how to counter fluctuations resulting from various factors. To adequately cover the load, efforts are made to regulate and improve the performance of the converter by regulating the electrical power to suit this. The converter design is developed to provide the required voltage and current for efficient operation.